A implantação dos cursos de graduação na modalidade distância nas instituições estaduais de ensino superior do Paraná, após a Lei de Diretrizes e Bases da Educação Nacional de 1996 - Zanutto, Edson Luis (2016)
The Directives and bases of national education-LDBN, nº 9.394, December 20th 1996, sets in its article 80, the possibility of using the Distance Learning in all teaching level, which later started being carried out by private initiative, becoming the most increasing teaching method in the country. The aim os this survey is to investigate which problems and hurdles make difficulties to this modality implantation in the Institution of Higher Education of Paraná State. IEES-PR, after 20 year that mentioned LDBEN has been aproved, only 6% of those courses are offerred by distance. The aim is to contribute to a critical reflection on it and present viable proposals for the consolidation of Higher Distance Education in these institutions. The methodology was the qualitative research, using as sources the biographic researches, analysis of official documents, as well as structured interviews. The theory of Pierre Bourdieu fields was used as a theoretical basis for this thesis. A feature present in all social fields that Bourdieu studied is the division between dominant and dominated the first dictating the rules of operation of the field, while the dominated struggle to improve their position. Interviews were accomplish ed with the coordinators of Distance Education of the respective IEES, who were ahead of issues related to the modality, as well as the Rector of the State University of Londrina, for analysis of the hypotheses that were supposed hindering the related implantation. Analyzing the hypotheses according to granted interviews, it is note up that they are relevant and can be justified by Bourdieu's theory. So, according to the raised related analysis by the interviewed people, we can have possibles suggestions to the cosolidation of modalities in those institutions